Do consumers understand PCP car finance? An experimental investigation - Terry McElvaney; Pete Lunn; Féidhlim McGowan (The Economic and Social Research Institute (ESRI), 2018)
A Personal Contract Purchase (PCP) plan is an innovative, complex and increasingly popular form of car finance. Consumers pay a deposit and monthly payments, but instead of paying off the total value of the car, they pay off the depreciation over a specified term. We used an experiment to investigate comprehension of PCP plans and scope for improving it through information disclosure and consumer advice. A representative sample of consumers (n=100) completed choice tasks, product rating tasks and multiple choice questions to measure the accuracy of consumers' decisions and extent of comprehension. Disclosures designed to improve the processing of mileage and cost information varied between participants. The tasks were also undertaken before and after reading an advice document. The results revealed poor understanding of PCP plans based on information typically disclosed by car dealers. Participants also made mistakes, often rating objectively worse offers more favourably than superior ones. The alternative disclosures were ineffective, but consumer advice sheets did improve comprehension and reduce mistakes. A sheet with a graphical explanation outperformed one with only text. We conclude that the complexity of PCP plans raises issues of consumer protection and that policymakers might consider stronger regulation.
Keywords: C91; D18; D91; G41; 330; Personal Contract Purchase (PCP); explanatory diagram; decision-making; comprehension